Development of myopia as a hazard for workers in pneumatic caissons. Issue 11 (1st November 2002) - Onoo, A; Kiyosawa, M; Takase, H; Mano, Y
Abstract : Background/aim: Pneumatic caisson engineering has been developed for large civil engineering constructions. Because of complaints of blurred vision by personnel working in pneumatic caissons, the development of myopia was suspected. The aim of this study was to determine the cause of the blurred vision and the mechanism underlying the changes. Methods: 12 caisson workers underwent a complete ophthalmological examination after completing up to 11 weeks of work (4 days/week) in a pneumatic caisson. Six months later, nine of the workers were examined again. Results: Nine subjects were myopic at the initial examination, and seven of these were considered to have developed the myopia after starting to work in the pneumatic caisson. Six months after completion of the work, the mean refractive change was significantly towards hyperopia. Conclusions: The blurred vision in pneumatic caisson workers was in all likelihood due to the development of myopia. The refractive shift towards hyperopia after completion of work in the pneumatic caisson supports this and demonstrates that the changes were temporary. The myopia is similar to the myopia seen in patients treated by hyperbaric oxygen. Careful monitoring of the refraction of caisson workers should be performed for industrial health control.